Recent developments in punitive damages in civil law, common law, the interamerican human rights system and international law (2019)
This article pretends to give account of the recent evolution in the application of the figure both in countries of the continental law, in which a tendency can be identified in favor of incorporating this way of appreciating the damages in areas like the protection of consumers, environment or Human Rights, and in the other hand, the tendency in the common law of the United States to establish limits to this sanctions, considering them in many cases excessive and disproportionate. © 2019 Universidad Externado de Colombia. All rights reserved.